Suffering Of Life Raised Theological Scepticism In “Bless Me Ultima” By Rudolfo A. Anaya - Minderop, Albertine (UI Scholars Hub, 2018)
The aim of this research is to show that the novel of “Bless Me, Ultima” (1972) written by Rudolfo A. Anaya contains theological scepticism as the impact of life suffering that experienced by the children’s characters. Sufferings of life that happened to the children are: killing, illness, poverty, and injustice. The implication of scepticism is some conflicts. The method used in this research is Content Analysis and the technique of Hermeneutics. Content Analysis is used to explore the ideas expressed by the author in the forms of statements, questions, and dialogues of the characters or the narrator. This method is to uncover, to understand, and to grasp the message of literary works. The method of interpretation used in this research is the techniques of Hermeneutics (theory of interpretation). According to Ricoeur, hermeneutics is the best strategy to interpret the texts of philosophy and literature. The research design are the understandingand interpretation of the characters’ way of thinking. Coherence is to understand the meaning of the element structure, internal relations to integrate all the elements to get the deepest meaning. Analogy is the observation of meaning and values, and describe their results through analysis by using some concepts. The result of this research are sentences and phrases that shows suffering of life, scepticism towards faith, and the implication of being sceptical. The conclusionof the research: Harsh treatment faced by Florence as a result of his blasphemous character. Although Anaya clearly illustrates the views of lives, thoughts, feelings, and hopes of this children's character, but he makes Florence a tragic figure. He was drowning in the lake and died.